HATI-HATI ANCAMAN TINDAK PIDANA PENCEMARAN NAMA BAIK DI MEDSOS DALAM UU ITE NOMER 11 TAHUN 2008 - Prasetyo, Yogi (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2021)
The purpose of writing is to provide an understanding to the public about the susceptibility of being caught in the crime of defamation in the electronic transaction information law, so that in carrying out their activities on social media, they must be careful. So that people are free from the trap of criminal defamation on social media. People who have carried out many activities on social media must understand in depth the contents of the offenses contained in the electronic transaction information law which are prone to legal threats. In this paper, we use a normative legal study method that understands law as a positive legal system in statutory regulations. While the approach used is legal philosophy. The main materials used in this study are laws and regulations and other legal materials that support the theme of the study. The analysis was carried out descriptively to obtain a general description of the legal issues being studied. The results showed that there were several legal problems committed by someone who could be classified as a criminal act of defamation, so that they could be threatened with the electronic transaction information law